Ethnic demonstration and cultural representation: From multiculturalism to cultural hybridization, the case of Mizrahi-Sabras in Israel - Shimoni, Baruch (Hagar: Studies in Society and Culture, 2007)
In this paper, I examine the cultural identity of Mizrahi-Sabras, second- and third-generation Israeli Jews from Arab and Muslim lands. I find them to be a hybrid of their parents 'cultural characteristics and those of the dominant Israeli Ashkenazim. I describe both my own cultural identity and that of contemporary Mizrahi-Sabrasingers, who produce contemporary Muzica Mizrahit, a hybrid musical form.